Can Biofluids Metabolic Profiling Help to Improve Healthcare during Pregnancy?. Issue 5 (11th July 2012) - Graça Graça, Gonçalo Gonçalo; Diaz Diaz, Sílvia O. Sílvia O.; Pinto Pinto, Joana Joana; Barros Barros, António S. António S.; Duarte Duarte, Iola F. Iola F.; Goodfellow Goodfellow, Brian J. Brian J.; Galhano Galhano, Eulália Eulália; Pita Pita, Cristina Cristina; Almeida Almeida, Maria do Céu Maria do Céu; Carreira Carreira, Isabel M. Isabel M.; Gil Gil, Ana M. Ana M.
Abstract : This paper describes a metabonomics study of 2nd trimester biofluids (amniotic fluid, maternal urine, and blood plasma), in an attempt to correlate biofluid metabolic changes with suspected/diagnosed fetal malformations (FM) and chromosomal disorders as well as with later occurring gestational diabetes mellitus (GDM), preterm delivery (PTD), and premature rupture of membranes (PROM). The global biochemical picture given by the threesome of biofluids should enable the definition of potential disease signatures and unveil potential metabolite markers for clinical use in predictive prenatal diagnostics. Results show that relatively strong metabolic disturbances accompany FM, reflected in all three biofluids and thus suggesting the involvement of both fetal and maternal metabolisms. Regarding GDM, amniotic fluid and maternal urine seem potential good media to detect early metabolic changes, and PTD subjects show small metabolite changes in the same biofluids, undergoing work being focused on plasma composition. Chromosomal disorders show an interestingly marked effect on maternal urine, whereas no statistically relevant early changes have been observed for PROM subjects. Interestingly, in the case of FM and chromosomal disorders, maternal biofluids show some sensitivity to disorder type, for example, for central nervous system malformations and trisomy 21, respectively. These results show the usefulness of biofluid metabonomics to probe overall metabolic disturbances in relation to prenatal disorders.